2019
DOI: 10.1017/s1759078719000163
|View full text |Cite
|
Sign up to set email alerts
|

SIW resonator fed horn mounted compact DRA with enhanced gain for multiband applications

Abstract: A novel design of compact and light-weight horn mounted cylindrical dielectric resonator antenna (CDRA) fed by substrate integrated waveguide (SIW) resonator has been investigated for high gain and multiband applications. SIW resonator contains two closely spaced longitudinal slots of equal length and unequal width to excite the CDRA. These slots are responsible for introducing triple resonating bands. The excited mode in dielectric resonator by longitudinal slots is EH11δ mode. The achieved impedance bandwidt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Electric field (E‐field) distribution of PD at 5.8 and 6.1 GHz frequency is analyzed and shown in Figure . It can be monitored that the propagating mode is similar to hybrid mode, that is, EH 11δ like‐mode for the entire operating band in reference to the corresponding cylindrical resonator mode …”
Section: Parametric Analysis and Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electric field (E‐field) distribution of PD at 5.8 and 6.1 GHz frequency is analyzed and shown in Figure . It can be monitored that the propagating mode is similar to hybrid mode, that is, EH 11δ like‐mode for the entire operating band in reference to the corresponding cylindrical resonator mode …”
Section: Parametric Analysis and Results Discussionmentioning
confidence: 99%
“…It can be monitored that the propagating mode is similar to hybrid mode, that is, EH 11δ like-mode for the entire operating band in reference to the corresponding cylindrical resonator mode. 20 The reflection coefficient vs frequency for all optimized antenna of each step are shown in Figure 14. Similar, Figure 15 shows the impedance variation vs frequency of PD in which it can be observed that the magnitude of the average impedance is around 50 Ω within most of the operating band.…”
Section: Metamaterials Design and Optimizationmentioning
confidence: 99%
“…In [11], a compact and light weight SIW antenna was reported. To improve gain a horn mounted cylindrical dielectric resonator was used.…”
Section: Introductionmentioning
confidence: 99%